Slavery of Indonesian Migrant Fishers: a Review of Regulation and Its Implementation - Nur, Muhammad (Yustisia, 2021)
According to the 2018 Global Slavery Index, migrant workers in the maritime and fisheries industry are as the second-ranked sector with the worst modern slavery practices among other work sectors in the world. This article aimed to analyze why many cases of modern slavery experienced by migrant fishers from Indonesia, and what stakeholders should do to improve the protection system for migrant fishers from Indonesia. The author uses normative juridical research methods. The data collection method used is the literature study. The results of this study found that the high number of cases affecting migrant fishers from Indonesia is caused by various governance weaknesses that have occurred so far. These weaknesses occur both at home and abroad. These weaknesses start from policy to implementation in the field and has resulted in cases of violations against migrant fishers that continue to this day. This paper provides some protection model and recommendations for improving the governance of placement and protection for the migrant fishers, namely: 1. Supervision System Improvement; 2. Improvement of the data collection system for Indonesian migrant fishers; 3. Increasing and developing foreign cooperation; 4. Increasing socio-economic reintegration programs; 5. Ratification of the Work in Fishing Convention 2007.